Graphene–CNT composite as catalyst support for microwave-assisted hydrogen releasing from liquid organic hydride. (6th July 2017) - Shi, Liujie; Liu, Xiaojun; Tuo, Yongxiao; Xu, Jing; Li, Ping; Han, Yifan
Abstract: A series of composites comprised of graphene (rGO) and carbon nanotube (CNT) with various weight ratios of them have been synthesized. The catalytic performance of the Pt catalysts supported on the rGO–CNT composites has been evaluated in the dehydrogenation of liquid organic hydride (decalin) for hydrogen releasing and compared with that of Pt/rGO and Pt/CNT catalysts. Both microwave irradiation and conventional heating methods have been adopted for the reaction. The structural and surficial features of the composites and rGO as well as CNT have been characterized by means of several techniques. The thermal behaviour of different carbon materials under microwave irradiation has been measured. The results show that there is an optimal CNT weight content in the composites leading the Pt/rGO–CNT0.17 catalyst to the best performance that cannot be achieved by the other catalysts including Pt/rGO and Pt/CNT as well. This has been ascribed to the most plentiful interface formed between rGO and CNT of a proper content, which is beneficial to the deposition of the Pt nanoparticles having the highest catalytic activity. Additionally, the strong coupling effect of carbon materials with microwave irradiation gives rise to better catalytic performance in comparison to conventional heating due to its capability to induce higher reaction temperatures. Nevertheless, the intrinsic catalytic properties of the Pt catalysts supported on different carbon materials are independent on the heating modes. Graphical abstract: Highlights: A series of composites comprised of graphene (rGO) and carbon nanotube (CNT) have been synthesized. Pt/rGO–CNT catalysts have been used in decalin dehydrogenation for hydrogen release under microwave irradiation. Maximum reaction rate has been obtained over the Pt/rGO–CNT catalyst with an optimum CNT content. The optimum CNT content provided the most plentiful interface between rGO and CNT for depositing Pt nanoparticles. The intrinsic activity of various catalysts is independent on the heating modes.